2020
DOI: 10.18378/cvads.v9i7.6834
|View full text |Cite
|
Sign up to set email alerts
|

Liofilização e caracterização físico-química de blend composto por kiwi e maracujá

Abstract: Os Blends constituem-se como uma importante alternativa para o processamento de frutas, agregando maior valor econômico e nutricional ao produto. Objetivou-se através do presente estudo o desenvolvimento de um blend liofilizado à partir das polpas de kiwi e maracujá, avaliar as suas características físico-químicas. O blend das duas frutas (in natura e liofilizado) foram carcaterizados quanto aos seguintes parâmetros físico-químicos: teor de umidade, atividade de água, sólidos solúveis totais (SST), acidez tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Gomes et al (2019) worked with blends composed of pineapple, carrots and cabbage sweetened with honey, the authors observed levels of total soluble solids ranging from 11.23 to 13.53 °Brix. Ribeiro et al (2019) analyzed kiwi blends with passion fruit and obtained levels of total soluble solids 12.0 and 55.66 °Brix for fresh and freeze dried, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Gomes et al (2019) worked with blends composed of pineapple, carrots and cabbage sweetened with honey, the authors observed levels of total soluble solids ranging from 11.23 to 13.53 °Brix. Ribeiro et al (2019) analyzed kiwi blends with passion fruit and obtained levels of total soluble solids 12.0 and 55.66 °Brix for fresh and freeze dried, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…O processo de secagem promoveu um aumento nos teores de açúcares redutores de 4,04% glicose para 23,92% glicose e não redutores de 1,61% sacarose para 5,32% sacarose esse aumento pode estar relaciona devido ao uso dos agentes espumantes. Barros et al (2019) obtiveram para polpa de abacaxi teores de 4,83% de glicose para açúcares redutores e 2,67% de sacarose para açúcares não redutores.…”
Section: Líquidounclassified
“…Koroishi (2005) validated this information regarding the use of the orange juice process. The same for Ribeiro et al (2019), studying the lyophilization and physical-chemical characterization of a blend composed of kiwi (Actinidia deliciosa) and passion (Passiflora edulis) fruits.…”
Section: Lbfpe and Olbfpe Samplesmentioning
confidence: 99%